Electronic business : a Canadian Perspective for a Networked World - Lee, In, 1958- (Hershey PA : Information Science Reference, 2003)
"This set of books offers a research compilation from over 250 international authors in the field of e-business"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electronic commerce